Аутсорсінгова модель реалізації корпоративної соціальної відповідальності - Звонар, В.П. (Інститут демографії та соціальних досліджень НАН України, 2009)
У статті обґрунтовано необхідність і визначено шляхи використання аутсорсінгу корпоративної соціальної відповідальності в соціальній політиці України. Основним
аргументом на користь такого аутсорсінгу є надзвичайна складність (а відтак – і ресурсоємність) процесу управління програмами корпоративної соціальної відповідальності. Використання різних форм (насамперед, повної та часткової) аутсорсінгу корпоративної соціальної відповідальності має найбільшу перспективу на регіональному рівні здійснення соціальної політики – в структурі фондів розвитку громади. В статье обоснована необходимость и определены пути использования аутсорсинга корпоративной социальной ответственности в социальной политике Украины. Основным аргументом в пользу такого аутсорсинга служит чрезвычайная сложность (а значит – и ресурсоемкость) процесса управления программами корпоративной социальной ответственности. Использования разных форм (прежде всего, полной и частичной) аутсорсинга корпоративной социальной ответственности имеет наибольшую перспективу на региональном уровне осуществления социальной политики – в структуре фондов местного развития. The paper argues the necessity and defines means of application of outsourcing to corporate social responsibility (CSR) in social policy of Ukraine. As CSR (corporate charity) is a secondary
(not-product-related) activity to any for-profit organization, the allocation of recourses (human, managerial, financial etc.) to this activity may decrease effectiveness of the major (productrelated)
functions, lessening the competitive ability of an enterprise. Initiation of specialized CSR-departments within an organizational structure (in order to provide expenditure control, feedback control and social effect monitoring) is a luxury, which most businesses in Ukraine can not afford. CSR-ignoring practices contradict imperatives of conventional modern business rules (e.g. sustainable development doctrine), which have presented CSR as a “must” for prosperous firms and successful for-profits throughout the world. Ukraine is also involved in the deployment of those imperatives as a new market economy country. Taking the burden of CSR-caused extra costs off a firm, outcontracting of CSR may contribute to wide spreading of corporate philanthropy, thus providing social policy and social-oriented activities in Ukraine with potentially essential assets. The paper derives, that deployment of CSR-outsourcing will produce the best effect on the
regional level of social policy of Ukraine – within community foundations as community-based non-profit organizations, usually established in an area to help solving local social problems
through accumulation and distribution chiefly local resources, aimed for social projects and programs of different kind.